Nontotally symmetric trifurcation of an SN2 reaction pathway. Issue 5 (29th October 2015) - Harabuchi, Yu; Ono, Yuriko; Maeda, Satoshi; Taketsugu, Tetsuya; Keipert, Kristopher; Gordon, Mark S.
Abstract : A new type of reaction pathway which involves a nontotally symmetric trifurcation was found and investigated for a typical SN 2‐type reaction, NC ‐ + CH3 X → NCCH3 + X ‐ (X = F, Cl). A nontotally symmetric valley‐ridge inflection (VRI) point was located along the C 3 v reaction path. For X = F, the minimum energy path (MEP) starting from the transition state (TS) leads to a second‐order saddle point with C 3 v symmetry, which connects three product minima of Cs symmetry. For X = Cl, four product minima have been observed, of which three belong to Cs symmetry and one to C 3 v symmetry. The branching path from the VRI point to the lower symmetry minima was determined by a linear interpolation technique. The branching mechanism is discussed based on the reaction path curvature and net atomic charges, and the possibility of a nonotally symmetric n‐furcation is discussed. © 2015 Wiley Periodicals, Inc. Abstract : A new type of reaction pathway which involves a nontotally symmetric trifurcation was found and investigated for the SN 2‐type reaction, NC ‐ + CH3 X → NCCH3 + X ‐ (X = F, Cl). A nontotally symmetric valley‐ridge inflection (VRI) point was located along the C 3 v reaction path. The branching path from the VRI point to the lower symmetry minima was determined. The possibility of a nontotally symmetric n‐furcation is discussed.